Himpunan keputusan dan instruksi Menteri Transmigrasi dalam rangka Rapat Kerja Teknis Departemen Transmigrasi, 1985 (Sekretariat Jenderal, Departemen Transmigrasi, 1985)
Collection of decrees and instructions of the Minister for Transmigration regarding aspects of organizational structure, functions, and internal relations.